Estudio de factibilidad para la implementación de una empresa productora de aromas de contratipo para damas y su comercialización en la provincia de Loja - Apolo Sánchez, Gina Mariveth (2010)
The present project of feasibility is based in the necessities of the feminine population of the county of Loja with relationship to the sector of cosmetic and perfumery, offering the users an economic alternative of quality with a product of origin lojano of competitive level. The project, will have a useful life of ten years, its facilities will be located in the city of Loja, in the streets: Av. Salvador Bustamante Celi 30-70 and Homero Idrovo, for the access easiness toward the different points of the city and county. The design of the product of 30 and 50ml observes the recommendations of the plaintiffs, its attractive presentation converts it in preferable for the purchase decision. The economic calculations - financiers contemplate the tributary, labor and employer obligations according to the government's economic politicians, for their organization it is considered as Company of Limited Responsibility, and it stops their operation, the levels Legislative are determined, Executive, Advisory, Support and Operative